Forebrain Cholinergic Signaling Regulates Innate Immune Responses and Inflammation - Lehner, Kurt R.; Silverman, Harold A.; Addorisio, Meghan E.; Roy, Ashbeel; Al-Onaizi, Mohammed A.; Levine, Yaakov; Olofsson, Peder S.; Chavan, Sangeeta S.; Gros, Robert; Nathanson, Neil M.; Al-Abed, Yousef; Metz, Christine N.; et al. (Frontiers in Immunology, 2019)
The brain regulates physiological functions integral to survival. However, the insight into brain neuronal regulation of peripheral immune function and the neuromediator systems and pathways involved remains limited. Here, utilizing selective genetic and pharmacological approaches, we studied the role of forebrain cholinergic signaling in the regulation of peripheral immune function and inflammation. Forebrain-selective genetic ablation of acetylcholine release and vagotomy abolished the suppression of serum TNF by the centrally-acting cholinergic drug galantamine in murine endotoxemia. Selective stimulation of acetylcholine action on the M1 muscarinic acetylcholine receptor (M1mAChR) by central administration of the positive allosteric agonist benzyl quinolone carboxylic acid (BQCA) suppressed serum TNF levels in murine endotoxemia. This effect was recapitulated by peripheral administration of the compound. BQCA also improved survival in murine endotoxemia and these effects were abolished in M1mAChR knockout (KO) mice. Selective optogenetic stimulation of basal forebrain cholinergic neurons innervating brain regions with abundant M1mAChR localization reduced serum TNF in endotoxemic mice. These findings reveal that forebrain cholinergic neurons physiologically regulate innate immune responses and inflammation, suggesting the possibility that in diseases of cholinergic dysfunction this anti-inflammatory regulation can be impaired. These results also suggest novel anti-inflammatory approaches based on targeting forebrain cholinergic signaling in sepsis and other disorders characterized by immune dysregulation.